Corpus-Assisted Discourse Study of How Chinese and Foreign Media Construct China’s Digital Trade Opening-up - Song, Zihan (International Journal of Social Sciences and Public Administration, 2026)
This study employs corpus-assisted discourse analysis to examine how China’s digital trade opening-up is reported by one Chinese and three major Western English-language newspapers from 2023 to 2025. Taking Sinclair's five types of co-selection theory as the core framework, the findings show that while Chinese and Western media share a basic consensus in recognizing digital trade as a key arena of global competition, their discursive constructions differ markedly. This paper contributes to digital trade discourse studies by systematically mapping these contrasting media narratives, thereby enhancing understanding of China’s digital governance in global contexts.